Violência doméstica e desempenho escolar: desafios para o judiciário e para a educação especial - Pereira, Paulo Celso (2006)
Children, as well as women, the elderly and the disabled, are the preferential victims of violence. The child ca be a direct or indirect victim of such phenomenon (as in the case of children exposed to marital violence). Child maltreatment damages cognitive development and may be responsible for declines in academic performance. The aims of this study were: a) to characterize the school performance of victimized children referred to the Judicial System (Study 1), and b) to identify teachers and school principals views on domestic violence and inclusionary practices (Study 2). Twenty victimized children have participated in Study 1 (ten male and ten female), whose school performance were compared to their peers of the same classroon, gender, age, but without a history of family violence. Eighteen teachers and ten school principals participated of Study 2. Children from both groups were given three instruments: The Academic Performance Test, Parenting Styles Inventory and Raven s Progressive Matrices Test. The children gave samples of their notebook production. Children s mothers answered a family interview and the Revised Conflict Tactics Scales (CTS-2). Teachers and school principals also took part of an intervew. Teachers report cards were analyzed and teachers offered their impressions on student s academic performance. Results generally indicated inferior academic performance by the victimized children, when compared with their matched group, in spite of similar results in the Raven s Test for both groups. According to teachers, victimized children had inferior academic performance in relation to their non-victim peers, having in addition, more behavioral problems and aggressive behaviors. CTS-2 results indicated that most of the victimized chilren were exposed to marital violence; in most cases, the target of violence was the child s mother. The teachers and school principals demonstrated to have notions about domestic violence. In regards to school inclusion, their knowledge was found to be superficial. In addition, teachers showed some reservations about adopting inclusionary practices.